Côte nord de Sibérie, Jugorski Char (détroit de Yougor) / d'après la carte de l'Amirauté britannique publiée en 1937, Service hydrographique de la marine . 1939 (1947)
Corr. . 1947 Relief shown by hachures. Depths shown by bathymetric isolines and soundings.; Selected lights shown in orange.; Includes 1 inset map: Côte ouest de l'Île Vaigatch, Baie de Liamtchina Grayscale; 1:75,700